Effect of Telemedicine Follow-Up on Neonatal Outcomes: A Pre-Post Intervention Study - Hafiz Zeekash Ur Rehman Malik, Ammar Haider Gondal, Muhammad Tauseef Rauf, Bushra Tariq, Waqar Mushtaq, Muhammad Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Neonatal mortality and morbidity remain major public health concerns, especially in low- and middle-income countries. Objective: To evaluate the effect of a structured telemedicine follow-up program on neonatal outcomes using a pre-post intervention design. Methods: This pre-post interventional study was conducted at The Children’s Hospital Lahore from 1 Jan 2023 to 1 july 2023. A total of 185 neonates were enrolled consecutively. The participants were divided into two groups: a pre-intervention group (n = 92), which received standard post-discharge care, and a post-intervention group (n = 93), which received structured telemedicine follow-up. Results: Hospital readmissions were significantly lower in the telemedicine group (5.4%) compared to the control group (14.1%, p = 0.038). Emergency visits also declined (9.7% vs. 19.6%, p = 0.041). Mean daily weight gain was higher in the telemedicine group (29.6 ± 6.4 g/day vs. 25.1 ± 7.2 g/day, p = 0.005). Exclusive breastfeeding rates were improved (81.7% vs. 65.2%, p = 0.018), and immunization adherence increased (94.6% vs. 84.8%, p = 0.041). Caregiver satisfaction was significantly higher in the telemedicine group (87.1% vs. 63.0%, p < 0.001). Conclusion: It is concluded that telemedicine follow-up is effective in improving key neonatal health indicators and caregiver satisfaction. This approach offers a scalable solution for enhancing post-discharge neonatal care, particularly in settings with limited healthcare access. Keywords: Telemedicine, Neonatal, Outcomes, Intervention, Effect, Patients